2016
DOI: 10.5573/ieie.2016.53.9.118
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Direction and Distance of an Unknown Radiation Source Using RMC

Abstract: Rotating modulation collimator(RMC) is a remote sensing technique for a radiation source. This paper introduces an RMC system model and its image reconstruction algorithm based on Kowash's research. The reconstructed image can show the direction of a source. However, the distance to the source cannot be recovered. Moreover, the RMC image suffers from 180° ambiguity. In this paper, we propose a distance estimation method using two RMCs together with a solution to the ambiguity. We also demonstrate its performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In this paper, we mainly focused on the optimization of design parameters for the dual-particle imaging purpose, and on the demonstration of the feasibility to develop a dual-particle imager. We proposed a laminated mask design consisting of 1 cm thick Pb and 0.2 cm thick BPE, and we also developed the image reconstruction algorithm utilizing MLEM, to estimate spatial distributions of gamma-ray and neutron sources, on the basis of previous research (Shin et al 2016a(Shin et al , 2016b. In the present study, we used a bilaterally symmetric mask design for RMC, and observed the existence of an intrinsic artifact in the reconstructed image because of the 180°periodicity in the modulation pattern.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this paper, we mainly focused on the optimization of design parameters for the dual-particle imaging purpose, and on the demonstration of the feasibility to develop a dual-particle imager. We proposed a laminated mask design consisting of 1 cm thick Pb and 0.2 cm thick BPE, and we also developed the image reconstruction algorithm utilizing MLEM, to estimate spatial distributions of gamma-ray and neutron sources, on the basis of previous research (Shin et al 2016a(Shin et al , 2016b. In the present study, we used a bilaterally symmetric mask design for RMC, and observed the existence of an intrinsic artifact in the reconstructed image because of the 180°periodicity in the modulation pattern.…”
Section: Discussionmentioning
confidence: 88%
“…Even though MLEM is often considered as a robust method to these types of low-count high-noise problems, such a low-count measurement situation can sometimes bring about critical issues in the estimation of source distributions. Shin et al suggested a regularization method in the image reconstruction algorithm using MLEM to make better estimations on the source location by removing unnecessary artifacts (Shin et al 2016a(Shin et al , 2016b(Shin et al , 2017. The regularization method attempts to maximize the penalized likelihood by assigning an adaptive weight to each pixel.…”
Section: Discussionmentioning
confidence: 99%
“…One can obtain temporal modulation profiles from the number of counts collected in the radiation detector using RMC, and reconstruct an image of the radiation source from the profile. One of limitations for the typical RMC-based radiation imaging shown in figure 1 lies on the limited field-of-view (FOV) determined by the solid angle subtended by the front and rear masks, which requires multiple imaging systems to cover an extended region for radiation monitoring [9]. In this research, we applied two hemispherical masks for the incoming radiation collimation, as an…”
Section: Introductionmentioning
confidence: 99%